The right way to reform the EU emissions trading system: Alternatives to the market stability reserve - Mark A. Andor; Manuel Frondel; Stephan Sommer (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2015)
In the light of persistently low prices for allowances, there is much debate about reforming the EU emissions trading system. Based on a proposal of the European Commission, the EU plans to introduce the so called Market Stability Reserve in 2019: a mechanism that regulates the amount of allowances within the market by temporarily taking some of the allowances into a reserve. The Commission thereby aims at reducing the surplus and securing a higher market price for allowances. An alternative reform proposal is the introduction of a minimum price. This RWI position puts forward a third alternative: retaining the emissions trading system in its original form and reducing the surplus by a one-time adjustment. In 2014, 900 million allowances from the years 2014 to 2016 were back-loaded to be auctioned in the years 2019 and 2020. Instead, these allowances should be deleted. Furthermore, if necessary, the amount of allowances could be constantly decreased by reducing the cap more strongly than planned. Compared with the other reform options, retaining the emissions trading system in its original form has two major advantages: first, politically driven interventions are minimized and, second, free market prices exhibit a stabilizing effect for fluctuations caused by the business cycle.
Keywords: 330